Pencil Beam Spectral Measurements of Ce, Ho, Yb, and Ba Powders for Potential Use in Medical Applications - N. Martini; V. Koukou; C. Michail; P. Sotiropoulou; N. Kalyvas; I. Kandarakis; G. Nikiforidis; G. Fountos (Journal of Spectroscopy)
The aim of the present study was to obtain modified X-ray spectra, by using appropriate filter materials for use in applications such as dual energy X-ray imaging. K-edge filtering technique was implemented in order to obtain narrow energy bands for both dual- and single-kVp techniques. Three lanthanide filters (cerium, holmium, and ytterbium) and a filter outside lanthanides (barium), with low K-edge, were used to modify the X-ray spectra. The X-ray energies that were used in this work ranged from 60 to 100 kVp. Relative root mean square error (RMSE) and the coefficient of variation were used for filter selection. The increasing filter thicknesses led to narrower energy bands. For the dual-kVp technique, 0.7916 g/cm2 Ho, 0.9422 g/cm2 Yb, and 1.0095 g/cm2 Yb were selected for 70, 80, and 90 kVp, respectively. For the single-kVp technique 0.5991 g/cm2 Ce, 0.8750 g/cm2 Ba, and 0.8654 g/cm2 Ce were selected for 80, 90, and 100 kVp, respectively. The filtered X-ray spectra of this work, after appropriate modification, could be used in various X-ray applications, such as dual-energy mammography, bone absorptiometry, and digital tomosynthesis.